PENGARUH KINERJA KEUANGAN DAN UKURAN PERUSAHAAN TERHADAP REAKSI PASAR - Zaylani, Ahmad; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of Return on Assets (ROA), Return on Equity (ROE), and the firm size to the market reaction on food and beverage companies which are listed in Indonesia Stock Exchange in 2011-2013 periods. The research sample has been selected by using purposive sampling technique therefore 16 food and beverages companies (48 firm years) which meet the criteria have been selected as samples. The analysis technique has been done by performing multiple regressions with the SPSS program 16 version. Based on the result of the multiple regressions analysis with the significance level of 5%, therefore this research shows that: (1) H1 is return on assets (ROA) has an influence to the market reaction with its significance level is 0.046. It can be accepted because the value of t-count is 2.082 which show positive direction. (2) H2 is return on equity (ROE) has an influence to the market reaction with its significance level is 0.031. It can be accepted since the value of t-count is 2.127 which show positive direction, (3) H3 is the firm size which has an influence to the market reaction with its significance level is 0.039. It can be accepted since itâs the value of t-count is 2.110 show positive directions. Therefore, return on Assets (ROA), return on equity (ROE), and firm size have positive influence to the market reaction.Keywords: Return on Assets (ROA), Return on Equity (ROE), Firm Size and Market Reaction